2001
DOI: 10.2169/internalmedicine.40.671
|View full text |Cite
|
Sign up to set email alerts
|

Amebiasis in Japanese Homosexual Men with Human Immunodeficiency Virus Infection.

Abstract: Wereport cases of amebiasis in 6 human immunodeficiency virus (HlV)-positive male patients. Five were confirmed homosexualswhile one was suspected. Three patients had liver abscess and 5 had colitis with duration of 10 days to months. The patients with liver abscess showeda lower incidence of abdominal pain but a higher incidence of concomitant diarrhea. Drainage therapy was effective for rapid afebrile results. Twoinvasive colitis cases died from perforation. This may have been due to delayed diagnosis. Invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…7 Additional anecdotal cases have been described both in Europe and Asia. [14][15][16] At present, the possible implications determined by simultaneous presence of HIV have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…7 Additional anecdotal cases have been described both in Europe and Asia. [14][15][16] At present, the possible implications determined by simultaneous presence of HIV have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In the past year there were several published studies of amebiasis in HIV-infected individuals [14][15][16][17]. Japanese men who have sex with men have previously been observed to have a high prevalence of antiamebic antibodies indicative of prior E. histolytica infection.…”
Section: Amebiasis In the Hiv-infected Patientmentioning
confidence: 99%
“…Japanese men who have sex with men have previously been observed to have a high prevalence of antiamebic antibodies indicative of prior E. histolytica infection. Mitarai et al [15] reported six cases of amebiasis in HIV-infected men from Japan. Remarkably, five of the six cases were initially misdiagnosed and treatment delayed.…”
Section: Amebiasis In the Hiv-infected Patientmentioning
confidence: 99%
“…Homosexual behavior is another important risk factor for amebiasis as well as human immunodeficiency virus (HIV) infection. Although amebiasis in homosexual men in the United States is predominantly caused by asymptomatic E. dispar infection rather than by E. histolytica infection (3), E. histolytica infection is more frequently seen in homosexual men in East Asian countries such as Taiwan, Korea, and Japan (4)(5)(6)(7)(8). It was reported that 13.4-20.4% of Japanese homosexual men test positive for amebic antibodies, according to enzyme-linked immunosorbent assay (ELISA); this is surprising considering that the hygiene status of the country is rather high (9).…”
Section: Introductionmentioning
confidence: 99%